Analisis Faktor Yang Dapat Menyebabkan Terjadinya Technostress pada Karyawan - Rahadian Fitra Syakura; Diah Priharsari; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Technostress is one of the negative effects experienced by individuals due to the use of technology defined as a disease of modern adaptation caused by the inability to cope with new computer technology healthily. The negative effects of the use of this technology are also felt by employees caused by the use of information technology well and its use is increasing due to the Covid-19 pandemic. Workers who are supposed to come to the office and meet with colleagues are required to convert all their activities through communication software. The use of technology is needed to support work during the current pandemic, but this trend is becoming a new thing for some people. If employees experience technostress, their performance will decrease and employees cannot complete their work well. The Study objectives were to know the factors that can cause technostress in employees and how to reduce technostress from the individual side of the employee. Data collection is done qualitatively to employees of an organization by conducting semi-structured interviews. Data obtained from interview results are analyzed using thematic analysis methods. There are six stages in thematic analysis, including understanding data, data coding, finding themes, reviewing themes, defining and naming themes, and creating analytical results. The results of this study of employees of an organization experienced five technostress factors. The study also discusses how individuals deal with technostress in employees, namely self-efficacy and mindfulness.